An exploratory study on restaurants' organizational resilience the role of capitals, dynamic capabilities and business model innovation - Castañeda, Nicole Essielyn C.; Tumanan, Mary Anne (Quezon City University of the Philippines Diliman, 2025)
This exploratory study examined the role of capital resources, dynamic capabilities, and business model innovation in fostering organizational resilience in the restaurant industry, using a sequential mixed-methods approach. Quantitative data were gathered from 35 restaurant key decision-makers through surveys, which were then analyzed using descriptive statistics and structural equation modeling. Qualitative insights were derived from four semi-structured interviews, two of which were conducted with resilience experts. The findings revealed that economic and human capital, dynamic capabilities (such as sensing and seizing opportunities), and technological and product innovation contribute positively to organizational resilience. Key enablers also included unity of purpose, strong leadership, staff engagement, and effective partnerships. The study proposed a Trust and Train, Look, and Collaborate (TTLC) model, which emphasized strategic investment in economic and human capital, such as establishing crisis funds and implementing training programs, to strengthen both employee and organizational resilience. It recommends integrating new technologies and offerings to enhance adaptability and fostering a shared vision through participative decision-making and network building.
In partial fulfillment for the Degree of Master of Hotel, Restaurant and Institution Management
Thesis
Keywords: Organizational resilience; Crisis management; Restaurant management; Capital resources; Dynamic capabilities; rust and Train, Look, and Collaborate (TTLC).